A novel theoretical analysis for the determination of the noise parameters applicable to millimeter‐wave frequencies (invited). (9th January 2015) - Boglione, Luciano; Caddemi, Alina; Caddemi, Ernesto
Summary This paper describes in detail a novel, fully analytical technique for the determination of high frequency noise parameters. The technique can be applied at any frequency of interest because the requirement of an external tuner is dropped. The absence of an input tuner removes the practical constraint of operational bandwidth of the system and opens the door to the direct evaluation of noise parameters of active devices in frequency ranges currently inaccessible. The mathematical formulation at the basis of the present technique is applied to the Pospieszalski noise model and is described in detail. The new technique provides an analytical tool to determine the equivalent noise temperatures Tgs and Tds against measured data over a broad frequency range. Limitations and opportunities of the new technique are discussed including new insights into the Pospieszalski noise model. Copyright © 2015 John Wiley & Sons, Ltd.